Analisis Pengaruh Perubahan Kondisi Lahan terhadap Debit Sungai Menggunakan Program HEC-HMS (Studi Kasus DAS Alo, Kabupaten Gorontalo) - Satrio Fitrawan Maku; Barry Yusuf Labdul; Rawiyah Husnan (Transbahasa, 2025)
The Alo Watershed (DAS Alo) is a-subwatershed of the Limboto Watershed loacted in Gorontalo Regency, covering an area of 210,495 km2. Frequent flooding in the Alo Watershed has caused significant damage, with various contributing factors including high rainfall, low public awareness of environmental issues, and sparse vegetation cover. To assess the impact of land condition changes on river discharge in the Alo Watershed, the Hydrologic Engineering Centre - Hydrologic Modelling System (HEC – HMS) program was employed, utilizing the Soil Conservation. The analysis using HEC-HMS program revealed that the discharge under 2019 land use conditions was higher than that projected in the 2032 Regional Spatial Plan (RTRW). To reduce future discharge, land use management was simulated by decreasing certain land uses, which were reallocated to other types of use, while adhering to the 2032 RTRW guidelines. The simulation of land use management under Scenario 1, with a return period of T years, succeeded in reducing flood discharge by 8,65%-14,67% compared to the 2019 conditions. Scenario 2 achieved a reduction of 8,43%-14,70%. Both scenario effectively reduced flood discharge beyond the 2019 conditions, indicating the potential of these strategies to mitigate future flood risks.